Detoxification response in honey bee larvae exposed to agricultural intensification - Macri, Ivana Noelia (2025)
Honey bee Apis mellifera colonies located in agroecosystems are exposed to pesticides and more fragmented habitats. The resources that bees obtain in these environments may be exposed to agrochemicals, which can accumulate in their colonies and be distributed among their nest mates. Hives placed in an agricultural setting located in the region of the Argentine Pampas were studied. Changes in the expression levels of insect cytochrome P450s, enzymes involved in the detoxification of xenobiotics, and the presence of pesticides in hive products at different times of crop management were evaluated. Our results showed that CYP6AS2 and CYP6AS4 expression in honey bee larvae increased significantly after crop flowering and pesticide application. Furthermore, residues of the herbicides atrazine and glyphosate, and the insecticide chlorantraniliprole were found in beeswax and honey samples collected from the same beehives, and their concentrations correlated with the expression profiles of CYP6AS2, CYP6AS3 and CYP9BD1. These results underscore the potential risks of pesticides exposure to larval development, highlighting the need to mitigate agrochemical use in agricultural landscapes to safeguard honey bee colonies.